Temporal Annotations for a Contextual Logic Programming Language} - Nogueira, Vitor (2009)
In this paper we propose the combination of modularity and temporal reasoning using logic programming as common ground. Moreover, we consider that the usage of a given module is influenced by temporal constraints, i.e. modularity and temporal reasoning are strongly connected. Besides illustrative examples, we also present the operational semantics and corresponding compiler for this language.